Artificial intelligence in foreign language learning: A bibliometric analysis - Yunus Doğan; Tarık Talan (Journal of Pedagogical Research)
Artificial intelligence [AI] has significant potential in foreign language learning and teaching, and various scientific studies that monitor, investigate, and examine developments in this field have been conducted for many years. In fact, with the increasing importance and popularity of AI, there has been an observed growth in the number of scientific studies in this area. However, this rapid development and expanding literature have created a wealth of information, making access to knowledge challenging for researchers and educators. Thus, this article reveals the use of AI in foreign language learning field with a detailed bibliometric analysis of the relevant research studies conducted between 2010-2023 in the Web of Science. Initially, the distribution of publications by year, citation counts, publication languages, and countries/regions was examined. Subsequently, information about the most cited articles, journals, authors, and countries related to the topic was presented. Furthermore, collaborations among authors, countries, and institutions involved in publications related to the topic were discussed. Finally, the frequency of keyword usage was examined, and a network structure was established to depict relationships between these keywords.